METHOD FOR IMPROVING BIOAVAILABILITY OF GLUCOSAMINES - OTSUKA, Yuta; TO, Hideto; TOMIMORI, Namino; TATEISHI, Norifumi (2019)
The purpose of the present invention is to improve the bioavailability of glucosamines. The present invention relates to a method for improving the bioavailability of glucosamines including having a subject orally ingest glucosamines after three or more hours of fasting and within six hours after the time when the amount of period gene mRNA expression peaks within a day. Le but de la présente invention est d'améliorer la biodisponibilité de glucosamines. La présente invention concerne un procédé pour améliorer la biodisponibilité de glucosamines, comprenant le fait d'avoir un sujet ingérer par voie orale des glucosamines après trois heures ou plus de jeûne et en six heures après le moment où la quantité d'expression de l'ARNm du gène de la période atteint son maximum en une journée 本発明は、グルコサミン類の生物学的利用率を向上させることを目的とする。 本発明は、３時間以上絶食後、かつ、Ｐｅｒｉｏｄ遺伝子のｍＲＮＡ発現量が１日の中で最大となる時間以降６時間以内に、対象にグルコサミン類を経口摂取させることを含む、グルコサミン類の生物学的利用率向上方法に関する。